Reiner-Philippoff model accompanied by a mass-based algorithm for hybrid bio-nanofluid flow over a nonlinearly-mutable wall - Dinarvand, Saeed; Nademi Rostami, Mohammadreza; Yousefi, Mohammad; Mousavi, Seyed Mehdi; Jabbaripour, Behzad; Noeiaghdam, Samad (Numerical heat transfer. Part B, Fundamentals, 2025)
Here, the mass-based hybridity method and the Reiner-Philippoff model are used in tandem to investigate the forced convection of Au-Cu/blood nanofluid flow over a nonlinear shrinking/stretching sheet with radiation and suction influences. It is claimed that the masses of base fluid (blood) and nanoparticles (Au and Cu) as an alternative to the nanoparticles volume fraction, according to the Tiwari-Das single-phase algorithm can be numerically implemented in the present problem using the finite difference method in the MATLAB software. The Prandtl number was chosen to 10, and the blood mass was set to 100 gr. Further, the range of nanoparticles is from 0 gr to 40 gr, the mutable sheet parameter is between −1.3 to 2, and for the Reiner-Phillippoff parameter its range varies from 0.1 to 1. In addition, it is proven that the governing equations of the present problem possess dual similarity solutions in a certain range of governing parameters. Findings show that the Reiner-Philippoff parameter limits the range of the suction impact of the shrinking sheet for which at least a solution is available. Results indicate that an increase in the suction parameter from 0 to 2 leads to an increment of about 109 % and 226 % for skin friction and heat transfer rate, respectively. Moreover, the dual solutions of this research only exist for the case in which the suction parameter of the surface sheet is greater than its critical value. Finally, in the numerous engineering applications where cooling technologies are crucial, new models for nanofluid hybridity can surely be very beneficial.